Assessment of Fluoride Content in Ground and Surface Water and its Environmental Impacts at Basavan-Bagewadi and Muddebihal Taluka of Bijapur District, Karnataka, India - M. S. Yadawe; SMT D. M. Hiremath; S. A. Patil (E-Journal of Chemistry)
An investigation was undertaken in 10 villages (28 samples) of Basavan-Bagewadi taluka and 11 villages (38 samples) of Muddebihal taluka of Bijapur district to assess fluoride and other physicochemical parameters. And also to assess the clinical symptoms like dental and skeletal fluorosis, joint pains and gastrointestinal diseases and to find out the severity of the disease. A check list developed with the help of available literature and in consolation with nutritionists was used to record clinical symptoms. A sample survey was made after examination for both sexes between the age of 8-50 years at Basavan-Bagewadi and Muddebihal taluka. Fluoride content varies from 0.40-6.40 mg/L and 1.10-7.10 mg/L. However 12 samples were within the range, while 16 samples were above the permissible limits at Basavan-Bagewadi Taluka where as in Muddebihal taluka all the values are above the permissible limits of WHO respectively. The results show that, out of the 2992 examined 824 (25.89%) people have dental and skeletal fluorosis, 274 (9.15%) people have joint pains, 167 (5.58%) have gastrointestinal discomfort and excessive thirst at different stages in Basavan-Bagewadi taluka. Among 2696 examined, 812(29.49%) people had dental and skeletal fluorosis, 432 (16.18%) people had joint pains, 415 (15.54%) people had gastrointestinal discomfort and excessive thirst at Muddebihal taluka of Bijapur district.